A MEDIATED MODEL OF LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: THE ROLE OF HUMAN RESOURCE DEVELOPMENT IN PUBLIC SECTOR ORGANIZATIONS - Pipit Juwita Nengsih; Djoko Setyadi; Irsan Tricahyadinata (RADJA PUBLIKA, 2025)
This study investigates the influence of leadership and the work environment on employee performance, with human resource development (HRD) serving as a mediating variable within a local government context. This research addresses the persistent issue of low employee productivity and limited professional growth in Indonesia's public sector, where leadership practices are predominantly transactional and developmental programs are underutilized. Employing a quantitative and explanatory approach, data were collected from civil servants at the Melayu Village Office, Tenggarong, East Kalimantan. The analysis utilized partial least squares structural equation Modeling (PLS-SEM) via SmartPLS 4. The results indicate that leadership has a significant positive effect on both HRD and employee performance, whereas work environment does not directly impact performance. Additionally, HRD mediates the relationship between leadership and employee performance but does not mediate the connection between the work environment and performance. These findings underscore HRD as a strategic mechanism by which leadership enhances employee outcomes. Theoretically, this study extends the human capital and transformational leadership frameworks to the public sector in developing countries. Practically, it emphasizes the importance of leadership-driven HRD programs in cultivating a competent, motivated, and high-performance workforce within local government institutions.